Composition material on the basis of a carbohydrate fiber matrix with immobilized insulin for the development of a new me dicine form: transdermal insulin plate - Sergeev, V.P.; Boshytska, N.V.; Klipov, V.D.; Protsenko, L.S.; Budilina, O.N. (Reports of the National Academy of Sciences of Ukraine, 2019)
The possibility of using an activated carbon fiber nanomaterial (ACFNM) as a matrix for the hormone insulin for the subsequent creation of an insulin patch for medical purposes is studied. As the carbon matrix, ACFNM obtained on the basis of hydrated cellulose fibers by their special chemicalthermal treatment by pyrolysis, is used. It is shown that AСFNM, due to its adsorption-desorption properties, actively immobilizes insulin and is a promising material for the further development of a transdermal patch. It is established that the intensity of sorption depends on the area of the carbon material. It is shown that active insulin passes into the aqueous solution from the surface of the carbon matrix during the first hour. It is shown that the film “3m Tegaderm Second Skin” (USA) slows down the release of insulin from the surface of the carbon matrix by ~ 1.5 times, which ensures a prolonged action of the hormone. It can be assumed that, by selecting a film with different porosities, close to the permeability of the human epidermis, it is possible to provide a dosed prolonged release of the hormone into the solution. Recommended: to use short-acting insulins in subsequent laboratory experiments that do not contain the crystalline phase in its composition; to select the optimal area of the carbon matrix, which will ensure, on the one hand, the adsorption of the insulin hormone in the required amount, on the other — complete coverage of the surface of VNM in order to exclude the processes of inverse sorption of insulin from a solution; to conduct an experiment, by using a thermostat at t = 36.6 0C.